Effects of Lipoic Acid on Walking Performance, Gait, and Balance in Secondary Progressive Multiple Sclerosis - Loy, Bryan D. (Complement Ther Med, 2018)
BACKGROUND: Gait and balance impairment is common in secondary progressive multiple sclerosis (SPMS). Lipoic acid (LA), an over-the-counter antioxidant, is effective in MS animal models and may improve walking speed, but effects on mobility are unreported. OBJECTIVE: Examine the effects of 1200 mg daily oral dose of LA versus placebo (PLA) on gait and balance in a 2-year, randomized, double-blind pilot study. METHODS: 134 participants were screened for eligibility before assignment to LA (n = 28) or PLA (n = 26). Included here were, 21 participants with SPMS who took LA (N = 11) or PLA (N = 10) capsules for 2 years (enrolled May 2, 2011 – August 14, 2015) and completed all tasks without the use of an assistive device. Participants completed the Timed Up and Go (TUG) and quiet standing tasks every 6 months while wearing inertial sensors (APDM Opals) to quantify mobility. RESULTS: LA had a medium effect on time to complete TUG at 2 years (g = 0.51; 95% CI = - 0.35, 1.38). In a subset of 18 participants with less disability (EDSS < 6, no use of ambulatory device), turning time was significantly shorter with LA (p = 0.048, ∆= 0.48 s). No differences in balance metrics were found between groups. CONCLUSIONS: LA had an effect on walking performance in people with SPMS, particularly in those with lower baseline disability.